Efektivitas Tata Kelola Administrasi Perpajakan Di Direktorat Penanganan Pelanggaran (Studi Kasus Direktorat Penanganan Pelanggaran Di Kementerian Kelautan Dan Perikanan Jakarta) - Multi Nopiatin; Winda Wulandari (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze the effectiveness of tax administration governance at the Directorate of Violation Handling. This research method is descriptive qualitative. Data collection techniques using observation, i nterviews and documentation. The informants in this study consisted of 5 (five) people who could provide information about the effectiveness of tax administration governance. The results of this study indicate that the effectiveness of tax administration g overnance at the Directorate of Violation Handling is quite effective where the management is in accordance with applicable tax laws and has used an electronicbased government system. In terms of the period of 1 (one) fiscal year 2022 in achieving the obj ectives of implementing tax administration, it has been said to be effective, but in terms of its objectives it has not been effective, seen from the secondary data owned, there are still records related to errors in inputting tax types, calculating tax am ounts and late tax payments. The importance of soci alization from tax officials at the Directorate General of Taxes related to increasing the ability of employees to understand effective tax administration governance, the need to attend tax classes both on line and offline organized by the Directorate Gener al of Taxes, and the addition of human resources who are experts and competent in taxation.